Identifikasi Skema Pencahayaan Terhadap Ketertarikan Pengunjung Pada Koridor Jalan Asia Afrika Bandung: Bahasa Inggris - Abdulhadi, Reza Hambali Wilman; Febriyanti, Santi; Sugihono, Erika Amerina (Program Studi Desain Interior Unikom, 2023)
Abstract: Public space is one of the most common areas in a city. In the urban area, the image arises from a variety of natural aspects, such as art, culture, history, made-to-measure architecture, facilities, and its infrastructure in public space. This research is aimed at the attraction of users towards street corridor and facade illlumination along Asia Afrika street corridor The analysis is done using quantitative methods in form of questionnaire toward the respondents. The results of this research show that the application of illumination at Asia Afrika Street corridor and building facade affect the attraction and interest of the visitors to the area. Keywords: attraction; city lighting; public space; street corridor; street illumination